Pengaruh Looseness Terhadap Vibrasi Peralatan Yang Mengalami Unbalance Dan Misalignment - ANDI KURNIAWAN (KILAT, 2021)
Looseness occurs in almost all machines and can changes the vibration of the machine. In this paper, experiments were conducted by using two sets of rotor model to observe the effects of looseness on vibration values and patterns on the spectrum of unbalance and misalignment conditions. Rotor model 1 was used to simulate unbalance condition by adding mass to the disk, while rotor model 2 was used to simulate misalignment by changing the position of the bearing housings. Looseness condition was achieved by loosening the bearing housing bolts. The result of vibration observations in unbalance machine showed that looseness changed the overall value and peak values of vibration spectrum. While in machine which has shaft misalignment condition, looseness changed the vibration patterns on the spectrum.